Enhancing Senior High School Students’ Critical Thinking and Graphical Representation Skills through an AR-Integrated Guided Inquiry E-Book in Thermodynamics - Bayu Aji Wicaksono; Heru Kuswanto (Universitas Negeri Yogyakarta, 2026)
This study addresses the persistent challenge of improving students’ higher-order thinking skills in physics, particularly critical thinking and graphical representation abilities, which remain relatively low in Indonesian high schools. To overcome this issue, a guided inquiry-based e-book integrated with Augmented Reality (AR) was developed and tested within the domain of thermodynamics. The research employed the ADDIE model, encompassing analysis, design, development, implementation, and evaluation stages, to ensure the systematic construction of the product. A quasi-experimental pretest–posttest control group design was applied with three groups: (1) guided inquiry-based e-book assisted by AR, (2) guided inquiry-based e-book without AR, and (3) conventional PowerPoint-based instruction. The product was validated by subject matter experts and practitioners, who confirmed its feasibility across material, media, and design aspects. Student responses indicated that the developed e-book was practical and engaging for classroom use. Effectiveness testing was conducted with 90 students using MANOVA, supported by prerequisite tests for normality, homogeneity, and multicollinearity. The results revealed significant improvements in both critical thinking and graphical representation skills, with the AR-assisted e-book outperforming the other instructional methods and achieving a moderate effect size. These findings highlight the pedagogical potential of integrating AR into guided inquiry-based e-books to foster interactive, student-centered learning environments. Furthermore, the study suggests that such innovations may serve as an effective alternative to traditional physics teaching methods and could be adapted for other physics topics beyond thermodynamics.